PEMANFAATAN TRAS DARI SAMIGALUH KULON PROGO SEBAGAI BAHAN POZOLAN UNTUK CAMPURAN MORTAR - Hariyanto, Ari Dwi; Satyarno, Iman; Widiasmoro, Widiasmoro (Civil Engineering Forum Teknik Sipil, 2009)
Cement is one of mortar components with significant influence to mortar quality and production cost. It is necessary to use alternative material as cement substitution material to reduce production cost without reducing the mortar quality. One of materials used as cement substitution is pozzolan. One type of pozzolan is Trass which is available in Kulon Progo Regency but has not been utilized optimally. The objective of this research is to obtain the mix ratio of lime-trass used as cement substitution in mortar production. This research used sand from Boyong, lime from Gunung Kidul, and trass from Samigaluh Kulon Progo. The chemical composition consised of active silica and trass petrography was used as secondary data. The primary data was the experiment result carried out in Construction Material Laboratory of Gadjah Mada University. The first step of experiment was to identify the mortar material characteristics. Then a paste mix in 4 ratios variation of mix lime-trasss (1:4, 2:3, 3:2, and 4:1) was made. Lime – trass mix ratio that produced the highest compression strength mortar (through compression test after 7 days) was used as cement substitution. Mortar mix ratio of cement (and cement substitution) and sand was 1 : 4. The Variations of cement : lime-trass were 1:0,1:4, 2:3, 3:2, 4:1, and 0:1. Result of the research showed that paste mix ratio of lime and trass of 2: 3 had the highest compression strength, which was used in the mortar mixes design. Results of mortar compression strength testing showed that the lower the compression strength, the larger the amount of the cement substitution. The mix of lime and trass taken from Pagerharjo can be used as cement substitution material for producing mortar type S to type O or concrete brick quality I to quality IV. Mix of lime and trass taken from Purwoharjo can be used as cement substitution material for producing mortar type N to type O or concrete brick quality I to quality III. Mortar tensile strength testing showed that the lower the tensile strength, the larger the cement substitution amount was. On the other hand, the larger the mortar permeability, the larger cement substitution amount was. Cement substitution can reduce the cement amount in mortar production but increase mortar production cost because trass production cost was more expensive than cement price.